Introducing Tuak, the Traditional Alcoholic Beverage of the Dayak Muara Tribe in Kalimantan, Indonesia: Gastronomy Identity Unveiled - Sari, Wiwik Nirmala; Elsty, Kezia (Mutiara: Multidiciplinary Scientifict Journal, 2024)
This research explores the potential of the traditional alcoholic beverage "Tuak" from the Muara Dayak Tribe in Pelindu Village, West Kalimantan, Indonesia, as a gastronomic tourism attraction. Drawing upon the Gastronomy Identity Model and qualitative descriptive methodology, the study delves into seven key components: flavor profiles, etiquette, recipes, fusion of ingredients and techniques, classic wine and food marriage, climate zones, and old and new world styles. Findings reveal that Tuak not only serves as a cultural and social symbol within the Dayak Muara community but also showcases unique production methods, knowledge transmission, and cultural essence. The study emphasizes the importance of considering Tuak as a potential culinary tourism product, contributing to the preservation of Indonesia's rich culinary heritage, and promoting sustainable livelihoods. Additionally, it highlights the challenges related to accessibility and infrastructure in the region, suggesting the need for further development to unlock Tuak's full gastronomic tourism potential.